Successive Inoculations of Pigs with Porcine Reproductive and Respiratory Syndrome Virus 1 (PRRSV-1) and Swine H1N2 Influenza Virus Suggest a Mutual Interference between the Two Viral Infections - Juliette Bougon (MDPI AG, 2021)
Porcine reproductive and respiratory syndrome virus (PRRSV) and swine influenza A virus (swIAV) are major pathogens of the porcine respiratory disease complex, but little is known on their interaction in super-infected pigs. In this study, we investigated clinical, virological and immunological outcomes of successive infections with PRRSV-1 and H1N2 swIAV. Twenty-four specific pathogen-free piglets were distributed into four groups and inoculated either with PRRSV at study day (SD) 0, or with swIAV at SD8, or with PRRSV and swIAV one week apart at SD0 and SD8, respectively, or mock-inoculated. In PRRSV/swIAV group, the clinical signs usually observed after swIAV infection were attenuated while higher levels of anti-swIAV antibodies were measured in lungs. Concurrently, PRRSV multiplication in lungs was significantly affected by swIAV infection, whereas the cell-mediated immune response specific to PRRSV was detected earlier in blood, as compared to PRRSV group. Moreover, levels of interferon (IFN)-α measured from SD9 in the blood of super-infected pigs were lower than those measured in the swIAV group, but higher than in the PRRSV group at the same time. Correlation analyses suggested an important role of IFN-α in the two-way interference highlighted between both viral infections.